2022
DOI: 10.21883/tp.2022.09.54678.58-22
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of structure of pulsed discharge in nitrogen and argon at different pressures in a "pin to plane" gap

Abstract: Using high-speed shooting and shadow photography, the spatial structure of a pulsed discharge in a 1.5 mm long "pin(cathode)-plane" gap in nitrogen and argon in the pressure range from 0.25 to 2 atm was studied. It has been found that a spark discharge is realized in nitrogen and a diffuse form of discharge is realized in argon. For both cases, the presence of a microstructure of discharges in the studied pressure range was found, when the discharge is an aggregation of a large number of micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Figure 3 shows the discharge shadowgrams at different time moments relative to the moment of the electrical breakdown. It can be seen that the discharge develops in a microchannel form, similarly to [19][20][21]. Recording of microchannels begins at the moment of breakdown near the pin, and they close the discharge gap in 2 ns after the breakdown.…”
Section: Experimental Equipment and Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…Figure 3 shows the discharge shadowgrams at different time moments relative to the moment of the electrical breakdown. It can be seen that the discharge develops in a microchannel form, similarly to [19][20][21]. Recording of microchannels begins at the moment of breakdown near the pin, and they close the discharge gap in 2 ns after the breakdown.…”
Section: Experimental Equipment and Resultsmentioning
confidence: 92%
“…The experimental setup for the discharge study is shown in figure 1. The experimental equipment and the shadow photography technique are described in detail in [19]. In general terms the experiments consisted of the following.…”
Section: Experimental Equipment and Resultsmentioning
confidence: 99%
See 3 more Smart Citations